Effect of PLTS power factor settings on power losses and voltage conditions in 20 kV medium voltage networks - Savira, Resti; Sudiarto, Budi (Jurnal Pendidikan Teknologi Kejuruan, 2023)
As technology develops, the rapid increase in PV capacity will affect the grid. This makes it important to determine the PV limit that can be injected into the grid defined as the PV Hosting Capacity (PVHC). In this paper, the author evaluates and analyses the impact of PV connections on medium voltage distribution lines (20kv) using ETAP 19.01 simulation. A medium voltage Grid with a capacity of 30MVA, has an industrial load varies from 650 kVA to 25 kVA with the total load capacity of 2225 KVA. The loads are supplied from two sources, grid and PV system. The simulation results state that the best of grid performance which provide the best losses and voltage condition when connecting 100% capacity of PV to the existing grid network is by setting the inverter power factor to 0.9. This setting will provide lowest power losses of 0,7 kW and improve the voltage value.